PROFIL PEMAHAMAN KONSEP PESERTA DIDIK SMP PADA MATERI KALOR DAN PERPINDAHANNYA - Hutomo, Bagus Addin; Suryaningsih, Yuliana; Subali, Bambang; Marwoto, Putut (Universitas Negeri Surabaya, 2020)
The heat and displacement is one of the material in science learning taught at the junior high school level. This study aims to describe the profile of the conceptual understanding of Class VIII junior high school students on matter of heat and displacement. The design of this study is a descriptive study concerning the understanding of the concept of junior high school students in material heat and displacement with a quantitative approach. The subjects in this study were 27 students of class VIII D Kesatrian 1 Semarang junior high school. The sampling technique uses probability sampling techniques with simple random sampling technique. The data collection method used is a test instrument in the form of a two-level multiple choice question that has been validated by experts. The results of this study found that understanding the heat concept and its displacement of 7% in the criteria were very low, as much as 26% in the low category, 48% in the medium category, 15% in the high category, and by 1% the criteria were very high. Based on the results of the research, it can be concluded that the percentage of understanding of the concept of heat material and its displacement is the largest in the medium category.